Mutations in CEP120 cause Joubert syndrome as well as complex ciliopathy phenotypes. Issue 9 (6th May 2016) - Roosing, Susanne; Romani, Marta; Isrie, Mala; Rosti, Rasim Ozgur; Micalizzi, Alessia; Musaev, Damir; Mazza, Tommaso; Al-gazali, Lihadh; Altunoglu, Umut; Boltshauser, Eugen; D'Arrigo, Stefano; De Keersmaecker, Bart; et al.
Abstract : Background: Ciliopathies are an extensive group of autosomal recessive or X-linked disorders with considerable genetic and clinical overlap, which collectively share multiple organ involvement and may result in lethal or viable phenotypes. In large numbers of cases the genetic defect remains yet to be determined. The aim of this study is to describe the mutational frequency and phenotypic spectrum of the CEP120 gene. Methods: Exome sequencing was performed in 145 patients with Joubert syndrome (JS), including 15 children with oral-facial-digital syndrome type VI (OFDVI) and 21 Meckel syndrome (MKS) fetuses. Moreover, exome sequencing was performed in one fetus with tectocerebellar dysraphia with occipital encephalocele (TCDOE), molar tooth sign and additional skeletal abnormalities. As a parallel study, 346 probands with a phenotype consistent with JS or related ciliopathies underwent next-generation sequencing-based targeted sequencing of 120 previously described and candidate ciliopathy genes. Results: We present six probands carrying nine distinct mutations (of which eight are novel) in the CEP120 gene, previously found mutated only in Jeune asphyxiating thoracic dystrophy (JATD). The CEP120-associated phenotype ranges from mild classical JS in four patients to more severe conditions in two fetuses, with overlapping features of distinct ciliopathies that include TCDOE, MKS, JATD and OFD syndromes. No obvious correlation is evident between the type or location of identified mutations and the ciliopathy phenotype. Conclusion: Our findings broaden the spectrum of phenotypes caused by CEP120 mutations that account for nearly 1% of patients with JS as well as for more complex ciliopathy phenotypes. The lack of clear genotype–phenotype correlation highlights the relevance of comprehensive genetic analyses in the diagnostics of ciliopathies.